Expression of geminin, p16, and Ki67 in cervical intraepithelial neoplasm and normal tissues. Issue 26 (June 2017) - Xing, Yan; Wang, Chaojun; Wu, Jie
Abstract : Abstract: Geminin is a protein involved in cell cycle progression. We aimed to evaluate the diagnostic value of geminin expression in cervical intraepithelial neoplasm (CIN). The expression of geminin, p16, and Ki67 was examined in 95 samples, including CIN1 (n = 45), CIN2/3 (n = 40), and normal cervical tissues (n = 10) by immunohistochemistry. The correlation between geminin or p16 expression and human papillomavirus (HPV) status was also evaluated. Geminin expression was negative in all normal tissues and expressed in 13.3% of CIN1 and 90.0% of CIN2/3. P16 expression was demonstrated in 24.4% of CIN1 and 87.5% of CIN2/3. The corresponding Ki67 expression was 35.6% and 95.0%. The specificity of geminin for differentiating between CIN1 and CIN2/3 was 86.7%, while for p16 and Ki67 the corresponding values were 75.6% and 64.4%. The sensitivity of geminin, p16, and Ki67 was 90.0%, 87.5%, and 95.0%, respectively. The positive predictive value (PPV) and accuracy of geminin were higher than p16 and Ki67. In addition, geminin expression showed a weak correlation with HPV status, but there was no association between p16 expression and HPV status. These results suggested that geminin had a high degree of sensitivity and specificity in determining CIN2/3. In addition to p16 and Ki67, geminin might be used as a new biomarker to distinguish between CIN1 and CIN2/3.